2020
DOI: 10.1038/s41467-020-14695-1
|View full text |Cite|
|
Sign up to set email alerts
|

Kea show three signatures of domain-general statistical inference

Abstract: One key aspect of domain-general thought is the ability to integrate information across different cognitive domains. Here, we tested whether kea (Nestor notabilis) can use relative quantities when predicting sampling outcomes, and then integrate both physical information about the presence of a barrier, and social information about the biased sampling of an experimenter, into their predictions. Our results show that kea exhibit three signatures of statistical inference, and therefore can integrate knowledge ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 76 publications
0
28
1
Order By: Relevance
“…F I G U R E 1 Examples of nonsymbolic ratio magnitudes. From left to right, line-ratios, circle-ratios, and dot-ratios animals such as monkeys (Drucker et al, 2016;Vallentin & Nieder, 2008), parrots (Bastos & Taylor, 2020), and chicks (Rugani et al, 2016) demonstrate this ability. For example, McCrink and Wynn (2007) found that infants who were habituated to multiple examples of a 2:1 ratio of different colored dots looked longer at novel 4:1 ratios, indicating that they could discriminate ratio magnitudes.…”
Section: Research Highlightsmentioning
confidence: 99%
“…F I G U R E 1 Examples of nonsymbolic ratio magnitudes. From left to right, line-ratios, circle-ratios, and dot-ratios animals such as monkeys (Drucker et al, 2016;Vallentin & Nieder, 2008), parrots (Bastos & Taylor, 2020), and chicks (Rugani et al, 2016) demonstrate this ability. For example, McCrink and Wynn (2007) found that infants who were habituated to multiple examples of a 2:1 ratio of different colored dots looked longer at novel 4:1 ratios, indicating that they could discriminate ratio magnitudes.…”
Section: Research Highlightsmentioning
confidence: 99%
“…The ability to reason about use probabilistic information to make predictions about uncertain events also appears to have evolved convergently in the great apes and parrots (Rakoczy et al, 2014;Bastos and Taylor, 2020). When choosing between two hidden samples taken from two mixed populations of rewarding and unrewarding objects, capuchin monkeys appear to use a heuristic strategy of simply avoiding the sample from the population with the greatest absolute number of unrewarding objects (Tecwyn et al, 2017).…”
Section: Differences In Intelligence Across Speciesmentioning
confidence: 99%
“…When choosing between two hidden samples taken from two mixed populations of rewarding and unrewarding objects, capuchin monkeys appear to use a heuristic strategy of simply avoiding the sample from the population with the greatest absolute number of unrewarding objects ( Tecwyn et al, 2017 ). On the other hand, both the great apes and the New Zealand mountain parrot, the kea, make their choices by relying on probabilistic information, by comparing the ratios of objects within and between the two populations ( Rakoczy et al, 2014 ; Bastos and Taylor, 2020 ). This ability, known as true statistical inference, has so far not been conclusively shown outside of these two taxa, as other studies on primates and birds have not been able to exclude the absolute number heuristic as a potential strategy ( Clements et al, 2018 ; Roberts et al, 2018 ; De Petrillo and Rosati, 2019 ; Placì et al, 2019 ).…”
Section: Differences In Intelligence Across Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of the infant study encouraged a series of comparative studies with other animals [ 8 13 ]. These studies are important to better apprehend the distribution of probabilistic reasoning skills and come to a better understanding of their evolution.…”
Section: Introductionmentioning
confidence: 99%